PREVENTIF KONFLIK MELALUI TRADISI SOWAN DILINGKUNGAN PONDOK PESANTREN AL-MUBAROK MIFTAHUL ULUM PARIT MASIGI SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Syarif Ali Al Qadrie (Jurnal Ilmiah Hospitality, 2022)
Conflict is an inseparable problem in every organization, especially in educational institutions such as Islamic boarding schools. Conflicts within Islamic boarding schools will become part of the organizational structure of an existing problem and need to minimize conflict which is the main task of a leader, as well as the joint responsibility of every individual in the Islamic boarding school environment. Based on these problems, research was carried out at the Al-Mubarok Miftahul Ulum Islamic boarding school, Sungai Ambawang, Kubu Raya Regency regarding conflict prevention through social media. This study aims to make the sowan tradition a medium in minimizing the level of prolonged conflict if a problem occurs in an Islamic boarding school environment involving all existing human resources. Researchers took data from the leadership and administrators as well as students at the boarding school which were obtained through interview techniques. The results of this study include: the leadership/kyai of the Al-Mubarok Islamic boarding school Miftahul Ulum has a strategy by maintaining friendship which has become a tradition of the Islamic boarding school which is often called sowan. Conflicts will slowly erode from individuals and groups within sowan law, so conflicts that occur slowly and will not become prolonged conflicts. Sowan is also carried out periodically both between meetings or deliberations and privately